2021
DOI: 10.3390/app11083717
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-Containing Polysaccharides—Structural Diversity, Biosynthesis, Chemical Modifications and Biological Activity

Abstract: Selenosugars are a group of sugar derivatives of great structural diversity (e.g., molar masses, selenium oxidation state, and selenium binding), obtained as a result of biosynthesis, chemical modification of natural compounds, or chemical synthesis. Seleno-monosaccharides and disaccharides are known to be non-toxic products of the natural metabolism of selenium compounds in mammals. In the case of the selenium-containing polysaccharides of natural origin, their formation is also postulated as a form of detoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 380 publications
(507 reference statements)
0
17
0
1
Order By: Relevance
“…The results of numerous studies on the effects of selenium incorporation into polysaccharides have indicated a significant increase in their biological activity, particularly immunomodulating, anti-cancer, and antioxidant effects [52]. In our previous study on the activity of water-soluble Se-polysaccharides isolated from the L. edodes mycelium, we have also observed significant activity enhancement related to the incorporation of selenium [20].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The results of numerous studies on the effects of selenium incorporation into polysaccharides have indicated a significant increase in their biological activity, particularly immunomodulating, anti-cancer, and antioxidant effects [52]. In our previous study on the activity of water-soluble Se-polysaccharides isolated from the L. edodes mycelium, we have also observed significant activity enhancement related to the incorporation of selenium [20].…”
Section: Discussionmentioning
confidence: 78%
“…Another interesting, but still poorly studied, problem is the selenium bonding to the structure of polysaccharides. When the chemical methods are used to enrich natural polysaccharides with selenium, the degree of oxidation of selenium and its bonding ability in Se-polysaccharides are easy to predict [52]. On the other hand, when using biotechnological methods for obtaining the Se-polysaccharides, these important structural features are practically unpredictable and impossible to reliably determine by simple spectral analysis methods (IR, UV, 13 C and 1 H NMR, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The results of numerous studies on the effects of selenium incorporation into polysaccharides have indicated a significant increase in their biological activity, particularly immunomodulating, anti-cancer, and antioxidant effects [ 18 ]. In our previous study on the activity of water-soluble Se-polysaccharides isolated from the L. edodes mycelium, we also observed significant activity enhancement related to the incorporation of selenium [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting, but still poorly studied, problem is the selenium bonding to the structure of polysaccharides. When the chemical methods are used to enrich natural polysaccharides with selenium, the degree of oxidation of selenium and its bonding ability in Se-polysaccharides are easy to predict [ 18 ]. On the other hand, when using biotechnological methods for obtaining the Se-polysaccharides, these important structural features are practically unpredictable and impossible to reliably determine by simple spectral analysis methods (IR, UV, 13 C and 1 H NMR, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation